P-P22 NET Profit: Considering quality of life assessment in patients treated with SSAs for NETs. (16th December 2021) - Hall, Lewis; Powell-Brett, Sarah; Thompson, Oscar; Bradley, Elizabeth; Smith, Stacey; Vickrage, Suzanne; Kemp-Blake, Joanne; Shah, Tahir; Roberts, Keith
Abstract: Background: Somatostatin Analogue (SSA) therapy of neuroendocrine tumours (NETs) leads to pancreatic exocrine insufficiency (PEI). PEI symptoms include diarrhoea, abdominal discomfort, bloating, and steatorrhea, which negatively impact quality of life (QoL). NETs (and the sequelae of carcinoid syndrome) however, have similar symptomatology to PEI, with a comparably negative impact on QoL. QoL tools exist to assess PEI and its response to enzyme therapy; however, we hypothesise that PEI symptom scale scores will be unreliable in SSA-induced PEI due to the concurrent improvement of the carcinoid symptoms. Methods: Adult patients commencing SSA therapy for NETs were recruited from December 2020. Qualitative assessments of the impact of SSAs and pancreatic exocrine function on patient QoL were performed before and during (at 8 weeks) therapy. The Pancreatic Exocrine Insufficiency Questionnaire (PEI-Q) was used to capture patient-reported assessment of relevant symptoms. Health-related QoL was assessed using the European Organisation Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLC)-C30, supplemented by the EORTC GI.NET.21. Patients were specifically asked about steatorrhea at both assessments. Results: Seven patients completed the study. 5-HIAA levels were raised in 4/7 patients, indicative of carcinoid syndrome, secondary to the NET. Pancreatic exocrine function reduced after SSA therapy in all patients (data reported elsewhere) but paradoxically PEI-Q symptom scale scores reduced (median decrease from baseline: -18.5%, range: -1.5- -55.6%; p = 0.018) (Figure 1 ). According to PEI-Q, all seven patients would meet the criteria for a mild PEI at baseline, and two would be considered severe. One patient reported steatorrhea after commencing SSA-therapy. No changes in relevant domains of EORTC questionnaires were statistically significant, including functional, symptomatic, and overall health scores. Conclusions: The PEI-Q tool is not useful for assessing SSA-related PEI due to substantial symptom overlap with the tumour itself and SSA therapy. The decrease in symptom score is likely due to improvement of carcinoid syndrome, independent of PEI. Although the cardinal PEI symptom is steatorrhea, there is no distinction between that and diarrhoea in the EORTC tool, and confounding aetiologies of diarrhoea in NET patients may further complicate assessment. Current available QoL measures are of limited use in the setting of SSA-related PEI, and care should be taken if evaluating PEI or response of PEI to treatment.